Coccospheres confer mechanical protection: New evidence for an old hypothesis. (15th September 2016) - Jaya, B.N.; Hoffmann, R.; Kirchlechner, C.; Dehm, G.; Scheu, C.; Langer, G.
Graphical abstract: Abstract: Emiliania huxleyi has evolved an extremely intricate coccosphere architecture. The coccosphere is comprised of interlocking coccoliths embedded in a polysaccharide matrix. In this work, we performed in-situ scanning electron microscopy based compression tests and conclude that coccospheres have a mechanical protection function. The coccosphere exhibits exceptional damage tolerance in terms of inelastic deformation, recovery and stable crack growth before catastrophic fracture, a feature, which is not found in monolithic ceramic structures. Some of the mechanical features of the coccospheres are due to their architecture, especially polysaccharide matrix that acts as a kind of bio-adhesive. Our data provide strong evidence for the mechanical protection-hypothesis of coccolithophore calcification, without excluding other functions of calcification such as various biochemical roles discussed in the literature. Statement of Significance: Although bio-mechanics of shell structures like nacre have been studied over the past decade, coccospheres present an architecture that is quite distinct and complex. It is a porous cell structure evolved to protect the living algae cell inside it in the oceans, subjected to significant hydrostatic pressure. Despite being made of extremely brittle constituents like calcium carbonate, our study finds that coccospheres possess significant damage tolerance especially due to their interlocking coccolith architecture. This will have consequences in bio-mimetic design, especially relating to high pressure applications.